Exploring key job demands and resources in Norwegian child mental health services: a cross-sectional study of associations with and relationship between compassion satisfaction, burnout, secondary traumatic stress and turnover intention - Samira Aminihajibashi; Tine K. Jensen; Tine K. Jensen; Ane-Marthe Solheim Skar; Ane-Marthe Solheim Skar (Frontiers Media S.A., 2024)
BackgroundBurnout, secondary traumatic stress, and high turnover rates among child mental health clinicians are a challenge, not only for the individual therapist and the organization but also for the successful implementation of evidence-based practices. However, little is known about which and how job-and implementation-related factors are associated with burnout, secondary traumatic stress, and turnover intention as well as compassion satisfaction among child therapists. In the present study, we aimed to explore these factors and related mechanisms by integrating the "professional quality of life" and the "job demands-resources" models of occupational health.MethodsWe measured the perceived professional quality of life and turnover intention among a national sample of 256 therapists working in Norwegian Child and Adolescence Mental Health Clinics (n = 44) that implemented Trauma-Focused Cognitive Behavior Therapy (TF-CBT). Seventeen Job-and implementation-related resources and demands were also measured using the General Nordic Questionnaire for Psychological and Social Factors at Work and the Implementation Component Questionnaire. Path analysis was used to test whether burnout and compassion satisfaction mediate the relationship between job demands and resources on one hand, and secondary traumatic stress and turnover intention on the other hand.Results and discussionResults revealed that two job resources, i.e., positive challenges at work and mastery of work, were significant predictors of all professional outcomes. The proposed model was only partly supported. That is, while burnout did mediate the relationship between some job demands (i.e., work-family interference and role conflict) and job resources (i.e., human resource primacy, positive challenges, and mastery of work) with secondary traumatic stress and turnover intention, compassion satisfaction did not mediate the relationship between job resources and turnover intention. Moreover, in addition to their indirect effects via burnout, role conflict and organizational climate (human resource primacy) also directly affected turnover intention. These findings propose that interventions that reduce burnout should be prioritized to improve the professional quality of life and turnover intention among child therapists. Theoretically, it seems that compassion satisfaction and work engagement act differently.